Draw the world! - Chambers, Catherine (Cambridge : Cambridge University Press, 2016)
Reader. Cambridge Reading Adventures is a ground-breaking Primary guided reading series which offers a great variety of engaging texts with international appeal. The series has been created by Cambridge University Press in collaboration with the UCL Institute of Education's International Literacy Centre. Each book is placed into reading bands, providing a gradient of challenge which helps accelerate learning to read. Teacher's notes are provided inside every book with full guidance to get the most out of every reading session.
Keywords: Drawing - Juvenile - literature; Juvenile - works